Holographic derivation of effective action for a dissipative neutral fluid - Yanyan Bu; Xiyang Sun (Journal of High Energy Physics)
Abstract Using a holographic prescription for the Schwinger-Keldysh closed time path, we derive the effective action for a dissipative neutral fluid holographically described by the Einstein gravity in an asymptotic AdS spacetime. In the saddle point approximation for the dual gravity, the goal is achieved by solving the double Dirichlet problem for the linearized gravitational field living in a complexified static AdS black brane background. We adopt a partially on-shell scheme for solving the bulk dynamics, which is equivalent to “integrating out” the gapped modes in the boundary field theory. The boundary effective action in the fluid spacetime, identified as the partially on-shell bulk action, is computed to first order in boundary derivative and to cubic order in AdS boundary data. The boundary effective action, rewritten in the physical spacetime, successfully reproduces various results known in the framework of classical hydrodynamics, confirming our holographic derivation.